Impact of fish oil supplementation on plasma levels of highly unsaturated fatty acid-containing lipid classes and molecular species in American football athletes - Veronica Anne Mullins; Justin M. Snider; Bryce Michael; Lydia Rose Porter; Roberta Diaz Brinton; Floyd H. Chilton (Nutrition & Metabolism)
Abstract Background Previous studies have linked sports-related concussions and repeated subconcussive head impacts in contact sport athletes to elevated brain injury biomarkers. Docosahexaenoic acid (DHA), the primary omega-3 (n-3) highly unsaturated fatty acid (HUFA) in the brain, has shown neuroprotective effects in animal models after brain injury, but clinical research has shown mixed results. Methods We conducted a randomized, double-blind, placebo-controlled study on 29 Division 1 collegiate American football players, exploring the impact of DHA (2.5 g) and eicosapentaenoic acid (EPA) (1.0 g) supplied as ethyl esters, on levels of plasma lipids shown to cross the blood-brain barrier. Dietary intake data was collected using food frequency questionnaires (FFQ). Complex lipids and unesterified fatty acids were isolated from plasma, separated via reversed-phase liquid chromatography and analyzed by targeted lipidomics analysis. Results FFQ results indicated that participants had low dietary n-3 HUFA intake and high omega-6 (n-6):n-3 polyunsaturated fatty acids (PUFA) and HUFA ratios at baseline. After DHA + EPA supplementation, plasma lysophosphatidylcholine (LPC) containing DHA and EPA significantly increased at all timepoints (weeks 17, 21, and 26; p < 0.0001), surpassing placebo at Weeks 17 (p < 0.05) and 21 (p < 0.05). Phosphatidylcholine (PC) molecular species containing DHA or EPA, PC38:6 PC36:6, PC38:7, PC40:6, and PC40:8, increased significantly in the DHA + EPA treatment group at Weeks 17 (and 21. Plasma concentrations of non-esterified DHA and EPA rose post-supplementation in Weeks 17 and 21. Conclusions This study demonstrates that n-3 HUFA supplementation, in the form of ethyl esters, increased the DHA and EPA containing plasma lipid pools the have the capacity to enrich brain lipids and the potential to mitigate the effects of sports-related concussions and repeated subconcussive head impacts. Trial Registration All deidentified data are available at ClinicalTrials.gov #NCT0479207.